Roles of Semivolatile/Intermediate‐Volatility Organic Compounds on SOA Formation Over China During a Pollution Episode: Sensitivity Analysis and Implications for Future Studies. Issue 8 (13th April 2021) - Wu, Liqing; Ling, Zhenhao; Shao, Min; Liu, Huan; Lu, Sihua; Zhou, Shengzhen; Guo, Junchen; Mao, Jingying; Hang, Jian; Wang, Xuemei
Abstract: To improve the performance of SOA simulations and to evaluate the roles of semivolatile/intermediate‐volatility organic compounds (S/IVOCs) on SOA formation with focus on a winter pollution episode, an updated S/IVOC emission inventory over China and optimized reaction parameterization were incorporated into a regional air quality model (i.e., the WRF‐Chem model). The simulation on atmospheric concentrations of SOA was improved with the inclusion of S/IVOC emissions and their degradation, wherein, the temporal mean bias between simulated and observed SOA concentrations decreased by 25%. With the updated S/IVOC emissions and chemical evolution parameterization, the fraction of observed SOA resolved by the model increased from 18% to 40%, of which 21% was attributed to the updated emissions while the remaining 1% was attributed to parameterization. The existence of discrepancy between observation and simulation indicated that other improvements are still needed for better simulation of SOA by the WRF‐Chem model. Using updated OH reactivity coefficient for polycyclic aromatic hydrocarbons and adding the O3 ‐initiated and NO3 ‐initiated oxidation of S/IVOCs did not significantly impact SOA formation. Model results further suggested that high SOA concentrations were mainly distributed in the Sichuan Basin, the eastern and southern China, with higher concentrations observed at night rather than during daytime. Compared with the contributions of all precursors, SOA concentrations in China were dominated by those formed from S/IVOCs, which were more sensitive to S/IVOC emissions than other parameterizations. These findings highlight the roles of S/IVOCs in SOA formation over China and provide valuable insights for future SOA simulations. Key Points: S/IVOCs are the main contributor to secondary organic aerosol (SOA) formation in China Updated OH reactivity and addition of NO3 /O3 ‐initiated S/IVOC oxidation had insignificant impact on SOA formation SOA simulations were highly sensitive to S/IVOC emissions